Role of Pathya-Apathya in the Management of Prameha (Type-2 Diabetes Mellitus) (AYUSHDHARA, 2023)
Before starting management of any disease three important things to be kept in mind that is etiology, well planning, and Pathya-Apathya. Pathya–Apathya plays important role in the management of various disorders. Prameha is one of such disorder in which Pathya-Apathya affect its morbidity. Etiology, etiopathogenesis with clinical manifestation of Prameha are very well described in ancient textbook like Charaka Samhita, Sushruta Samhita, Astanga Hridyam and Astanga Samgraha etc. In all treatise of Ayurveda, Prameha is considered as Santarpanajanya Vikara that is of three types i.e., Vataj, Pittaj and Kaphaja. Madhumeha mentioned under the heading of Vataj Prameha that is closely correlated to diabetes mellitus. Diabetes Mellitus is of two type viz., Type-1 Diabetes & Type-2 Diabetes. Among that, Type-2 diabetes is non-insulin dependent diabetes mellitus that occur in middle age. In this clinical entity insulin resistance was developed. In its management, Pathya–Apathya contributes a major role in controlling blood sugar level. Therefore, author attempted to highlight role of Pathya–Apathya (do’s & don’t) in the management of Type-2 Diabetes Mellitus.